Grafting with Bone Substitute Materials in Therapy-Resistant Periapical Actinomycosis - Saeed Asgary; Leyla Roghanizadeh (Hindawi Limited, 2021)
Actinomycosis can be one of the causes of persistent periradicular lesions. This is the report of a patient who was first referred with complaint of pain in maxillary right incisors. A standard root canal therapy was carried out. Unluckily, the patient returned with recurrent symptoms; therefore, surgical endodontic retreatment was decided. While the large periradicular lesion was curetted, a whitish yellow granule-like material came out from the periapical area that was submitted for histopathological examination. The apices of both maxillary right incisors were resected. Root-end cavities were sealed with calcium-enriched mixture (CEM) cement. Finally, the remaining large defect was filled with natural bone substitutes. Since the histopathological diagnosis revealed actinomycotic infection, oral penicillin V was prescribed for four weeks. At two-year recall, the bone healing process was completed. Apical actinomycosis can cause therapy-resistant lesions. Root-end surgery employing CEM and bone substitutes might be an effective method to help bone healing in large periradicular lesions.